How Thai Undergraduate Nursing Students Learned to Develop Their Knowledge and Skills in Clinical Practice: A Grounded Theory Research Study - พงสุวรรณ, จิตตินันท์; Boddy, Julie; Woods, Martin; บาลทิพย์, กาญจน์สุนภัส (Princess of Naradhiwas University Journal, 2018)
This study used a Straussian grounded theory approach to explore the perspectives of 32 Thai undergraduate nursing students from all levels on the topic of how they developed their nursing skills in the process of caring for clients. Data were collected by using in-depth audio-taped interviews, as well as observations and field notes that enabled concurrent data validation with methodological triangulation. Following coding analysis of the data, an early emerging category related to the issue of continuing practical studies where being worried and afraid about practicing and being concerned about not understanding case problems were significant conditions that motivated the students’ learning. A second category emerged later in the analysis, namely learning how to provide nursing care, where supervisors’ expectations of students as learners within the hierarchical culture of Thai nursing was identified as the most powerful condition to motivate student learning. In some participants, an internal motivation, i.e. a desire to learn, marked them as successful learners. This enabled them to accomplish the full process of Developing Effective Strategies for Nursing Care, which emerged as the core category. The findings could be used to guide nursing instructors about how to enable the students to successfully integrate theory into clinical practice.